Effects of structure on flow mechanics in the human left ventricle and respiratory tract - Moore, Brandon L., author; Dasi, Lakshmi Prasad, advisor; Orton, Christopher, committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2011)
Cardiac and respiratory dysfunctions represent a large portion of healthcare problems in the United States. Many of these problems are caused by abnormal flow mechanics due to altered anatomical structure. This structure in the human body is very complex and ranges over many different scales. At relatively small scales, one facet that is still not well understood is the role of trabeculae on the biomechanics of the left ventricle. Similarly, large-scale airflow through the respiratory tract has not been fully investigated as a function of age or mechanical ventilation. This research has revealed some of the flow patterns caused by these different scale structures. Fractal geometry was used to help characterize the inner surface of the left ventricle at different times during the cardiac cycle. The fractal dimension of the ventricle was determined using a custom box-counting algorithm developed in MATLAB, and it was shown that trabeculae do indeed play a role in the biomechanics of heart pumping. Computational fluid dynamics (CFD) was also run on the respiratory tracts of three different patients to determine airflow effects due to age and intubation. Three dimensional models were constructed from computed tomography (CT) scans and simulations were run in ANSYS Fluent. Results of the study were validated through grid and time step sensitivity studies as well as comparison to previous studies. It was shown that flow mechanics in the airways of children change with age as well as with the introduction of an intubation tube.